Universal Noir #2 - Huggins, Roy 1914-2002; Metty, Russell 1906-1978; Stanwyck, Barbara 1907-1990; Preston, Robert 1918-1987; McNally, Stephen 1913-1994 (Universal Studios, 2023)
Ein verzweifelter Ehemann versucht, Hilfe für seine spielsüchtige Frau zu finden. [imdb.de]
Original: USA, 1949
Bildformat: 1,37:1
Keywords: Film; Blu-Ray-Disc